A systematical rheological study of polysaccharide from Sophora alopecuroides L. seeds. (15th January 2018) - Wu, Yan; Guo, Rui; Cao, Nannan; Sun, Xiangjun; Sui, Zhongquan; Guo, Qingbin
Highlights: Rheological properties of Sophora alopecuroides L. seeds polysaccharide were studied. Different rheological models were applied. Shear thinning flow behavior and viscoelastic property of SAP were demonstrated. Rheological properties of SAP with other reported polysaccharides were compared. The application of SAP was proposed. Abstract: The rheological properties of polysaccharide (SAP) from Sophora alopecuroides L. seeds were systematically investigated by fitting different models. The steady flow testing indicated that SAP exhibited shear-thinning behaviors, which were enhanced with increasing concentration and decreasing temperature. This was demonstrated quantitatively by Williamson and Arrhenius models. According to the generalized Morris equation, SAP exhibited random coil conformation with the potential to form weak gel-like network. On the other hand, multiple results of dynamic tests confirmed the viscoelastic properties of SAP, showing oscillatory behaviors between a dilute solution and an elastic gel. Furthermore, SAP solutions were thermorheologically stable without remarkable energetic interactions or structural heterogeneity, since their rheological patterns were successfully applied to Time-temperature superposition (TTS) principle, modified Cole-Cole analysis and Cox-Merz rule.